Robinson Crusoe in the family : feminist economics and lost in space - Hewitson, Gillian J., 1961- (Discussion papers (La Trobe University. School of Business), 2001)
The use of the figure of Robinson Crusoe as an exemplar of rational economic man may be viewed as of no significance whatsoever, or as very significant in the creation of the meaning of the economic agent. This paper discusses two alternative views of feminist economists. Some feminist economists can be understood to be arguing for the situating of Crusoe within a family context in order to more fully represent the economic reality of both men and women. Others suggest that adding representations of women and families without examining the underlying significance and functioning of Crusoe as a self-made man may misrepresent women in the same way as their exclusion or absence from economic representations. A reading of a modern Family Robinson story is used to discuss these views.